Occupational Mobility in American Business and Industry, 1928-1952 - Warner, W. Lloyd (William Lloyd), 1898-1970; Abegglen, James C. (Book collections on Project MUSE., 1955)
Occupational Mobility in American Business and Industry, 19281952 was first published in 1955. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Is the American occupational system rigid or flexible? How has it changed in the last twenty-five years? What factors help to influence the selection of business leaders? Questions like these are answered in this comprehensive study of occupational mobility, made by two social scientists at the University of Chicago. The study is based on information about 8,000 executives in the largest business firms of America. The rate of movement of men from various occupational backgrounds into positions of business leadership today is compared with that of 1928, as reported in the well-known study of Taussig and Joslyn, American Business Leaders. Warner and Abegglen present their complete research data, many of the findings in tabular form. The research encompasses all kinds of businesses and industries in every part of the country and persons at all levels of top management.